AB1084 Preliminary results of the use of serum calprotectin (MPR8/MPR14) in clinical practice in paediatric rheumatology. (12th June 2018) - Magallares López, B.; Martínez-Martínez, L.; Hernandez Lafuente, M.C.; Molto Lacosta, E.; Alvaro Gargallo, Y.; Park, H.S.; Castellví, I.; Millán Arciniegas, M.; Díaz-Torné, C.; Moya, P.; Laiz, A.; Casademont, J.; et al.
Abstract : Background: Serum Calprotectin is a new biomarker of clinical activity in Rheumatology, especially in Juvenile Idiopathic Arthritis (JIA) Objectives: To assess the use of serum Calprotectin in paediatric patients with inflammatory/Rheumatic diseases in clinical practice Methods: We retrospectively collected Demographic and Clinical data from patients of our Paediatric Rheumatology Clinic, in which serum Calprotectin levels were determined. The determination of serum Calprotectin was carried out using the ELISA technique. Diagnostic and Inflammatory activity data were also collected: RCP, ESR and Clinical Assessment of the patients Results: We present 28 patients, 61% females, with an average age of 11 (3–23 years) The diagnoses were as follows: 16 JIA (57% of the total), of which 8 were of the Oligoarticular type, 3 were Polyarticular, 3 were Arthritis related to Enthesitis, 1 was Psoriatic and 1 Systemic. Other diagnoses were: Behçet, 1 Autoinflammatory Diseases: 4 (2 ADA2 Deficit, 1 Familial Mediterranean Fever, 1 PFAPA) and 7 patients had suspected rheumatological/inflammatory diseases in study 17 patients were considered clinically inactive, 6 with inflammatory activity and 3 doubtful at the time of blood test. The mean values of Calprotectin, RCP and ESR can be seen in Table 1. Calprotectin was statistically correlated with Clinical Activity (p=0.018), however, neither ESR (p=0.539) nor RCP (p=0.059) did, although in RCP there was a clinical trend, (ANOVA) Calprotectin, RCP and ESR were negative in 91%, 80% and 76% respectively of Inactive patients; and positive in 43%, 100% and 33% of the Active ones The analysis of the ROC curves in our sample showed that the value that allows to discriminate between active and non-active disease with a Sensitivity of 80% and a Specificity of 69% is 2'07 µg/mL Serum Calprotectin was 2 points higher in the group of patients with Autoinflammatory diseases than in the group of JIA, with a mean of 4.91 compared to 2.90 (p=0.002). However, since it is a retrospective study, we must bear in mind that this can be influenced by the reasons for the test request, being in the group of Autoinflammatory Disease the suspicion of active disease, and in the AIJ simply monitoring or assessment of treatment optimisation. It should be noted that, in the patients in diagnostic process that did not present any rheumatological disease (final diagnoses of: arthralgias in 3 cases and glomerulonephritis not associated to rheumatologic/autoimmune disease in 1), serum Calprotectine did not exceed in any case the 1.15 µg/mL Conclusions: Serum Calprotectin is emerging as a useful marker, not only in the field of JIA, but also in other diagnostic groups such as Autoinflammatory Diseases. Prospective and larger studies are needed to determine its role Disclosure of Interest: None declared